The impact on the sport ball - Rudakov, R. N.; Podgaets, R. M. (Russian Journal of Biomechanics, 2005)
The rebound of the spherical sport ball from an impactor or a motionless plane has been considered on the basis of classic impact theory. The cases of the impact on motionless or moving ball have been studied. The general theory has been developed that allows calculating the velocity of the ball`s mass centre and its angular velocity after impact.